LINGUOCULTURAL CHARACTERISTICS OF ANTHROPONYM - Tilovova Guzal Rustamovna (Journals Park Publishing, 2022)
The subject of modern linguo-cultural studies are linguistic signs formed as a result of the cooperation of different codes - language and culture. Each linguistic entity is also a cultural entity. Therefore, language signs are also the "language" of culture and indicate the national-cultural identity of the language owner. At this point, it should be mentioned that even if all grammatical rules are obeyed, there may be some "cultural barriers".
Keywords: anthroponyms, cultural color, analogy in anthroponyms, nomination.